Steroid hormone analysis by LC-MS/MS - Hakkola, Salla (fi=Turun yliopisto|en=University of Turku|, 2017)
Latest advances in LC-MS/MS technology have changed the field of steroid hormone analysis. Steroid hormone related diseases, such as congenital adrenal hyperplasia (CAH), can be now diagnosed more reliably by liquid chromatography – tandem mass spectrometer techniques, instead relying on already dated immunoassays. Newborn screening programs are in more and more general use in hospitals and increasing number of patients can be treated before the symptoms occur. Steroid hormone analysis has also advanced in areas of doping analysis, quality control of meat industry and environmental health. This thesis represents the biosynthesis, structures, properties and function of steroid hormones and investigates the optimal methods to analyze steroids by LC-MS/MS system. Thesis is written in cooperation with Wallac Oy to improve their newborn screening product, CHS™ MSMS Steroids Kit, and therefore is the study of the Kit’s steroids of interest underlined. Different sample pretreatment techniques are discussed and compared. Optimal liquid chromatography conditions for steroid hormone analysis are investigated and optimal methods and equipment of mass spectrometry analysis are represented and compared and the typical challenges of mass spectrometry analysis are discussed. Also immunoassay techniques are presented, of the historical point of view. Experimental part focuses on finding an optimal sample preparation method, by comparison of liquid-liquid and solid phase extraction techniques. The goal of the experimental part was to improve the assay procedure (LC-MS/MS) of CHS™ MSMS Steroids Kit for quantitative steroids analysis in biological matrix (serum) in order to obtain more precise and sensitive assay procedure. Also, the goal for the improvements of the method was to find simple and not too expensive assay procedure for routine use in a typical analytical laboratory.